Systematic Literature Review of Factors Influencing Food Away from Home (FAFH) Consumption in Asia: Drivers, Behaviours and Societal Implications - Shahida, Siti Nur; Saili, Abdul Rahman; Mottaleb, Khondoker A.; Santoso, Dwi Budi; Pangestuty, Farah Wulandari; Oblomurodov, Narzullo Naimovich; Ulugbekovich, Achilov Mashrab; Abdullaevna, Karieva Gulnora; Fatah, Fazleen Abdul (Research on World Agricultural Economy, 2026)
Over the past twenty years, Asia has gone through major demographic, economic, and technological changes that have reshaped how people eat, with one of the clearest shifts being the growing dependence on Food Away from Home (FAFH) meals prepared or consumed outside the household. This systematic literature review (SLR) brings together empirical studies published between 2000 and 2025 that shape FAFH consumption and utilises the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method to examine the critical drivers, behaviours, and social impacts influencing FAFH across Asian countries. The review systematically categorises the studies into five major themes: (1) economic and demographic factors, (2) health and nutritional effects, (3) environmental and technological influences, (4) sociological and cultural aspects, and (5) policy and governance responses. Overall, the findings show that eating practices across Asia are shifting toward more convenient and calorie-dense meals, although still shaped by cultural norms, food-safety perceptions, and the rapid growth of digital platforms. The trend became even more noticeable after 2019 with the rise of online food-delivery services linked to COVID-19. Research shows that in most Asian countries, people spend more on FAFH as their income rises, and studies suggest that eating FAFH might link to health issues. Although the expansion of FAFH has supported job creation and service-sector growth, it also brings challenges for food-security goals, and sustainable food-system development.. Notably, this review demonstrates how Asian food consumption is changing and highlights the need for more integrated policy frameworks to achieve food security goals. ER